Pengaruh Penambahan Tepung Kulit Melinjo dalam Pakan Terhadap Peningkatan Kualitas Warna Ikan Guppy (Poecilia reticulata) - Dinda Prasetya Oktaviani Dinda; Andri Nofreeana; Eric Armando (Universitas Mataram, 2024)
Carotenoids that are added to feed can improve the color quality of fish because they cannot synthesize the color in their bodies. This research aimed to determine the effect of adding Melinjo Fruit Peel Flour on feed to enhance the color quality of Guppies. The experiment used a completely randomized design with five treatments (Melinjo Fruit Peel Flour 0%, 2,5%, 5%, 7,5%, and 10%) and three replications. Data were analyzed using analysis of variance (ANOVA) and significantly different between treatments were analyzed using Duncan's test. The results showed that the addition of 10% Melinjo Fruit Peel Flour on feed had a significant effect to enhance the color quality of Guppies 2,26% in orange and 3,05% in blue. The results showed that the addition of 10% Melinjo Fruit Peel Flour on feed gives the best growth with a weight of 0,32 g/head, length of 0,60 cm/head, and survival rate of 95,8%.